A ROS-responsive conductive hydrogel and a preparation method and application thereof
Patent Information
- Application Number
- CN202411757925.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2044-12-03
AI Technical Summary
[0004]本申请公开了一种具有ROS响应的导电水凝胶及其制备方法和应用,旨在解决现有ROS响应水凝胶敷料存在多重响应、无法精确的对ROS进行响应的技术问题
[0020]本申请提供的制备方法通过将巯基化透明质酸和5-羟甲基糠醛构成单层水凝胶网络的含有硫缩醛键化合物,再与丙烯酰胺、N,N'-亚甲基双丙烯酰胺、过硫酸铵与导电介质进行交联反应制成;一方面,能够实现ROS的精确响应,当在高ROS环境下,导电水凝胶中的硫缩醛化学键中的硫原子会失去电子,被氧化为硫氧化物形成电子转移,这些电子的移动形成电流信号,可实现创面的实时监测,实现慢性创面的诊疗一体化。同时,ROS响应的硫缩醛化学键会在创面炎症期响应ROS断裂,并释放5-羟甲基糠醛,缓解炎症反应,进而促进伤口愈合;另一方面,通过交联反应能够赋予水凝胶优异的机械性能和生物相容性,确保在发挥性能的同时水凝胶结构不会被破坏;与此同时,本申请的制备工艺简便,不需要特殊设备,易于实现批量生产与应用推广。
Smart Images

Figure CN119591794B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of medical biomaterials technology, and in particular relates to a ROS-responsive conductive hydrogel, its preparation method and application. Background Technology
[0002] Wound healing is a complex and delicate pathophysiological process, which can be divided into four typical stages: the coagulation / hemostasis stage, the inflammation stage, the new tissue formation stage, and the wound remodeling stage. However, chronic wounds often stagnate in the inflammation stage, accompanied by problems such as large amounts of exudate, severe infection, pain, and tissue necrosis. Once a chronic wound forms, the combined effects of persistent inflammatory response, oxidative stress, hypoxia-reoxidation, and fibrosis lead to a much higher level of reactive oxygen species (ROS) than normal skin tissue, thereby triggering chronic inflammation and creating a vicious cycle. Therefore, it is necessary to develop biomedical materials with excellent comprehensive performance to achieve efficient wound healing.
[0003] Current research typically utilizes the transduction properties of ROS signaling to develop ROS-responsive biomaterials to promote wound healing. For example, Professor Guo Baolin of Xi'an Jiaotong University (ROS-responsive hydrogels with spatiotemporally sequential delivery of antibacterial and anti-inflammatory drugs for the pair of MRSA-infected wounds, Regenerative Biomaterials, Volume 11, 2024, rbad110) prepared ROS-responsive hydrogel dressings by crosslinking hyaluronic acid-grafted 3-aminophenylboronic acid with phenylboronic acid ester bonds to polyvinyl alcohol, achieving the time-sequential release of two drugs for wound repair. However, these widely used ROS-responsive chemical bonds suffer from the limitation of multiple responsiveness, making it impossible to precisely respond to only ROS. Summary of the Invention
[0004] This application discloses a ROS-responsive conductive hydrogel, its preparation method, and its application, aiming to solve the technical problem that existing ROS-responsive hydrogel dressings have multiple responses and cannot accurately respond to ROS.
[0005] To achieve the above objectives, the technical solution of this application is:
[0006] The first aspect of this application provides a method for preparing a ROS-responsive conductive hydrogel, the method comprising:
[0007] Thiolized hyaluronic acid, 5-hydroxymethylfurfural, and trifluoroacetic acid were dissolved in water and reacted. After the reaction was completed, the mixture was purified by dialysis to obtain a compound containing a thioacetal bond.
[0008] The thioacetal-containing compound, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate were crosslinked with a conductive medium to obtain a ROS-responsive conductive hydrogel.
[0009] Preferably, in conjunction with the first aspect, the method for preparing the thiolized hyaluronic acid includes:
[0010] Hyaluronic acid, cystamine dihydrochloride, and 1-hydroxybenzotriazole hydrate were dissolved in polybutylene succinate. The pH was adjusted, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dithiothreitol were added to react. The mixture was then purified by dialysis to obtain thiolated hyaluronic acid.
[0011] Preferably, in conjunction with the first aspect, the pH value adjustment range is 7.5-8.5.
[0012] In conjunction with the first aspect, preferably, when the mercapto-modified hyaluronic acid, 5-hydroxymethylfurfural and trifluoroacetic acid are dissolved in water and then reacted, the reaction is carried out under light-protected conditions at room temperature.
[0013] Preferably, in conjunction with the first aspect, the percentage of acrylamide added is 16-26%.
[0014] Preferably, in conjunction with the first aspect, the amount of N,N'-methylenebisacrylamide added is 10% of the acrylamide monomer.
[0015] Preferably, in conjunction with the first aspect, the conductive medium is poly(3,4-ethylenedioxythiophene):polystyrene sulfonate; the amount added is 0.2-1%.
[0016] Preferably, in conjunction with the first aspect, when the compound containing thioacetal bonds, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate are subjected to a crosslinking reaction with a conductive medium, the reaction temperature is 60-80℃ and the reaction time is 1.5-4h.
[0017] The second aspect of this application provides a conductive hydrogel prepared by the preparation method described in the first aspect.
[0018] The third aspect of this application provides the application of conductive hydrogels prepared by the preparation method described in the first aspect or the conductive hydrogels described in the second aspect in the preparation of biomedical materials.
[0019] Compared with the prior art, the advantages or beneficial effects of the embodiments of this application include at least the following:
[0020] The preparation method provided in this application involves a compound containing thioacetal bonds forming a monolayer hydrogel network of thioacetal and 5-hydroxymethylfurfural, which is then cross-linked with acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, and a conductive medium. On one hand, this method enables precise response to reactive oxygen species (ROS). Under high ROS conditions, sulfur atoms in the thioacetal bonds of the conductive hydrogel lose electrons and are oxidized to sulfur oxides, resulting in electron transfer. This electron movement generates a current signal, enabling real-time monitoring of the wound and achieving integrated diagnosis and treatment of chronic wounds. Simultaneously, the ROS-responsive thioacetal bonds break during the inflammatory phase of the wound, releasing 5-hydroxymethylfurfural to alleviate inflammation and promote wound healing. On the other hand, the cross-linking reaction endows the hydrogel with excellent mechanical properties and biocompatibility, ensuring that the hydrogel structure is not damaged while maintaining its performance. Furthermore, the preparation process of this application is simple, requires no special equipment, and is easy to mass-produce and apply. Attached Figure Description
[0021] To more clearly illustrate the technical solutions of the embodiments of this application, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are only some embodiments recorded in this application. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.
[0022] Figure 1 The 1H NMR spectra of HA, HA-SH, and HA-TA-HMF provided in the embodiments of this application;
[0023] Figure 2 Infrared spectra of HA, HA-SH, and HA-TA-HMF provided in the embodiments of this application;
[0024] Figure 3 The above is a 1H NMR spectrum of the ROS-responsive compound HA-TA-HMF containing thioacetal bonds, as described in this application embodiment.
[0025] Figure 4 The diagram shows the responsive release of 5-hydroxymethylfurfural in the conductive hydrogel provided in the embodiments of this application.
[0026] Figure 5 The tensile stress-strain curves and compressive stress-strain curves of the conductive hydrogel provided in the embodiments of this application;
[0027] Figure 6 An electrical signal diagram showing the change of ROS concentration in the conductive hydrogel of group B provided in the embodiments of this application;
[0028] Figure 7Biocompatibility diagram of the conductive hydrogel provided in the embodiments of this application. Detailed Implementation
[0029] The technical solutions of the embodiments of this application will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some, not all, of the embodiments of this application. All other embodiments obtained by those skilled in the art based on the embodiments of this application without creative effort are within the scope of protection of this application.
[0030] In the following description of this embodiment, the term "and / or" is used to describe the association relationship between related objects, indicating that three relationships can exist. For example, A and / or B can represent: A existing alone, B existing alone, and A and B existing simultaneously. A and B can be singular or plural. The character " / " generally indicates that the preceding and following related objects have an "or" relationship.
[0031] In the following description of this embodiment, the term "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refer to any combination of these items, including any combination of single or multiple items. For example, "at least one of a, b, or c", or "at least one of a, b, and c", can both mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, and c can be single or multiple.
[0032] Those skilled in the art should understand that, in the following description of the embodiments of this application, the sequence of numbers does not imply the order of execution. Some or all steps may be executed in parallel or sequentially. The execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of this application.
[0033] The terminology used in the embodiments of this application is for the purpose of describing particular embodiments only and is not intended to be limiting of this application. The singular forms "a" and "the" as used in the embodiments of this application and the appended claims are also intended to include the plural forms, unless the context clearly indicates otherwise.
[0034] Those skilled in the art will understand that the numerical ranges in the embodiments of this application should be understood to specifically disclose each intermediate value between the upper and lower limits of the range. Each smaller range between any stated value and an intermediate value within the stated range, as well as any other stated value or an intermediate value within the stated range, is also included in this application. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0035] Unless otherwise stated, the technical / scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art described herein. While this application describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may be used in embodiments or test examples of this application. All references to this specification are generally incorporated herein by reference to disclose and describe methods and / or materials associated with said references. In the event of any conflict with any incorporated references, the content of this application shall prevail.
[0036] It should be noted that all raw materials and reagents in the embodiments of this application were purchased from the market or prepared according to conventional methods known to those skilled in the art.
[0037] In a first aspect, embodiments of this application provide a method for preparing a ROS-responsive conductive hydrogel, the preparation method comprising:
[0038] Thiolized hyaluronic acid, 5-hydroxymethylfurfural, and trifluoroacetic acid were dissolved in water and reacted. After the reaction was completed, the mixture was purified by dialysis to obtain a compound containing a thioacetal bond.
[0039] The thioacetal-containing compound, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate were crosslinked with a conductive medium to obtain a ROS-responsive conductive hydrogel.
[0040] On the one hand, it enables precise response to ROS. Under high ROS conditions, sulfur atoms in the thioacetal bonds of the conductive hydrogel lose electrons and are oxidized to sulfur oxides, resulting in electron transfer. This electron movement generates a current signal, enabling real-time monitoring of the wound and achieving integrated diagnosis and treatment of chronic wounds. Simultaneously, the ROS-responsive thioacetal bonds break during the inflammatory phase of the wound, releasing 5-hydroxymethylfurfural to alleviate the inflammatory response and promote wound healing. On the other hand, cross-linking reactions endow the hydrogel with excellent mechanical properties and biocompatibility, ensuring that the hydrogel structure is not damaged while maintaining its performance. Furthermore, the preparation process of this application is simple, requires no special equipment, and is easy to mass-produce and promote.
[0041] It should be noted that the 5-hydroxymethylfurfural used in this application exerts its anti-inflammatory effect by inhibiting MAPK, NF-κB and Akt / mTOR pathway-related proteins; at the same time, it has the ability to promote the proliferation and migration of skin fibroblasts, endowing the conductive hydrogel with good biocompatibility, excellent physicochemical properties, and the effect of accelerating wound healing.
[0042] In this embodiment, the preparation method of the thiolized hyaluronic acid includes: dissolving hyaluronic acid (HA), cystamine dihydrochloride (CA), and 1-hydroxybenzotriazole hydrate (HOBT) in polybutylene succinate (PBS), adjusting the pH, adding 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) and dithiothreitol (DTT) for reaction, and dialysis purification to obtain thiolized hyaluronic acid (HA-SH). Specifically, by thiolizing high molecular weight hyaluronic acid, the amino group in cystamine dihydrochloride reacts with the carboxyl group in hyaluronic acid, and the disulfide bond is broken to form thiolized hyaluronic acid. The introduction of the thiol group can promote the crosslinking reaction between hyaluronic acid and subsequent acrylamide. The specific reaction process is shown in formula (1):
[0043]
[0044] It should be noted that after dissolving thiolated hyaluronic acid (HA-SH), 5-hydroxymethylfurfural (5-HMF) and trifluoroacetic acid (TFA) in water, a compound containing a thioacetal bond (HA-TA-HMF) is obtained. The specific reaction process is shown in formula (2):
[0045]
[0046] It should be noted that the molecular structure of the conductive hydrogel prepared in this application is shown in formula (3):
[0047]
[0048] It should be noted that the anti-inflammatory properties of the conductive hydrogel are mainly achieved through hyaluronic acid and 5-hydroxymethylfurfural, while the ROS responsiveness of the gel system is achieved through thioacetal bonds. Its drug release rate is positively correlated with the ROS concentration, causing changes in different electrical signals, thereby achieving stable monitoring and realizing the integrated diagnosis and treatment of chronic wounds.
[0049] In this embodiment, the reaction of thiolated hyaluronic acid, 5-hydroxymethylfurfural, and trifluoroacetic acid dissolved in water is carried out under light-protected conditions at room temperature. Using light-protected conditions at room temperature simulates the environment within a living organism, allowing the reaction to proceed under optimal conditions, thereby maintaining a high reaction rate and efficiency.
[0050] In this embodiment, the percentage of acrylamide added is preferably 16-26%. By controlling the amount of acrylamide added, the hydrogel can be effectively endowed with excellent mechanical properties.
[0051] In this embodiment, the amount of N,N'-methylenebisacrylamide added is preferably 10% of the acrylamide monomer. N,N'-methylenebisacrylamide, as a crosslinking agent, can react with the active sites on the linear polymer chain through its two acrylamide groups to form a three-dimensional network structure, thereby improving the mechanical strength and stability of the material, and enhancing mechanical properties, controlling porosity and swelling degree, and improving thermal and chemical stability.
[0052] In this embodiment, the conductive medium is poly(3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS); the preferred addition amount is 0.2-1%. By controlling the amount of conductive medium added, the hydrogel can be endowed with excellent electrochemical properties while also possessing excellent mechanical properties.
[0053] In this embodiment, when the thioacetal-containing compound, acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, and conductive medium are subjected to a crosslinking reaction, the reaction temperature is 60-80°C and the reaction time is 1.5-4 hours. By controlling the time and temperature of the crosslinking reaction, sufficient contact between the reactants and the formation of chemical bonds are ensured, thereby endowing the hydrogel with excellent mechanical properties.
[0054] Secondly, embodiments of this application also provide conductive hydrogels prepared by the method described in the first aspect. The preparation method of this application can endow the conductive hydrogel with good ROS responsiveness, and its drug release rate is positively correlated with ROS concentration, causing changes in different electrical signals, thereby achieving stable monitoring, realizing integrated diagnosis and treatment of chronic wounds, alleviating inflammatory responses and promoting wound healing, while also possessing excellent mechanical properties and biocompatibility.
[0055] Thirdly, embodiments of this application also provide the application of conductive hydrogels prepared by the preparation method described in the first aspect or the conductive hydrogels described in the second aspect in the preparation of biomedical materials. Based on the above-prepared conductive hydrogels, which exhibit good ROS responsiveness and whose drug release rate is positively correlated with ROS concentration, they can alleviate inflammatory responses and thus promote wound healing. They also possess excellent mechanical properties and biocompatibility, and have broad application prospects in the preparation of biomedical materials.
[0056] The technical solution of this application will be further described below with reference to specific embodiments.
[0057] Example 1
[0058] This embodiment provides a method for preparing thiolized hyaluronic acid (HA-HS), specifically including:
[0059] Hyaluronic acid (HA) was dissolved in PBS. Cystamine dihydrochloride (CA) was then added to the solution (in excess molar amount relative to -COOH). After complete dissolution, 1-hydroxybenzotriazole hydrate (HOBT) was added (again, in excess molar amount relative to -COOH). The pH of the solution was immediately adjusted from 4.1 to 7.5 using 1M NaOH. 1-Ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) was added to the solution, and the mixture was stirred overnight at room temperature in the dark. The reaction solution was then dialyzed against deionized water for 3 days, and the pH was adjusted to 8.5. Dithiothreitol (DTT) was added to the solution, and the reaction was stirred overnight at room temperature in the dark. The pH of the reaction solution was adjusted to 3.5, and the mixture was dialyzed against deionized water for 3 days. After freeze-drying, the solution was stored in the dark under nitrogen atmosphere to obtain thiolized hyaluronic acid (HA-SH).
[0060] Example 2
[0061] This embodiment provides a method for preparing a compound containing a thioacetal bond (HA-TA-HMF), specifically including:
[0062] Thiol-modified hyaluronic acid (HA-SH) was dissolved in 100 mL of deionized water, and 5-hydroxymethylfurfural (5-HMF) was added and dissolved completely. Trifluoroacetic acid (TFA) was then added to the reaction solution, and the mixture was stirred overnight at room temperature in the dark. Subsequently, the reaction solution was dialyzed for 3 days, freeze-dried, and stored under nitrogen atmosphere in the dark to obtain the compound containing thioacetal bonds (HA-TA-HMF).
[0063] To verify the structural properties of the compound containing thioacetal bonds (HA-TA-HMF), the compound was characterized by NMR and IR spectroscopy, and the results are as follows: Figure 1-2 As shown.
[0064] according to Figure 1 The NMR spectra of HA, HA-SH, and HA-TA-HMF are shown. In these spectra, a and b represent double bond peaks in 5-HMF, with peaks appearing in the 5.5-6.3 ppm range. These double bond peaks represent the aldehyde double bonds in pentahydroxymethylfurfural, and the presence of superimposed methine groups at 4.3-4.7 ppm confirms the successful synthesis of the thioacetal bond. Since the attached 5-hydroxymethylfurfural contains a double bond, the observed phenomenon of this double bond peak on the NMR spectrum is the identification of the bond's attachment. Figure 1The marked part shows obvious small peaks. Because small molecules are connected to polymers, the peaks are not very high, which is normal. c: Characteristic peak of thioacetal bond (4.3-4.7ppm peak shape is superimposed and increased); d, e: Methylene peaks of modified thiolated hyaluronic acid. By comparing the chemical formula of HA, it can be seen that the thiolated modified hyaluronic acid has two more methylene groups and one HS. Therefore, the peak position of the methylene group should be found on NMR to prove the success of the modification. That is, the triplet peaks at positions d and e are the characteristic peaks of the methylene group. This can be clearly seen by comparing the NMR spectra of HA and HA-HS.
[0065] according to Figure 2 It can be seen that the infrared spectra of HA, HA-SH, and HA-TA-HMF are shown, where a) is the infrared spectrum of 500-4000 cm⁻¹. -1 Spectral diagrams within the range, b) are 500-2000 cm⁻¹ -1 The spectrum is within the range of [insert range here]. Chemical bonds such as C=C and CO on the small molecule 5-pentahydroxymethylfurfural can all be found in the graph: 1600-1750 cm⁻¹. -1 C=C stretching vibrations occur, and CO stretching vibrations occur at 1200-1000 cm⁻¹. -1 Deformation vibrations of double-bonded C-hydrogen atoms and aromatic hydrogen atoms in benzene rings: 1000-630 cm⁻¹ -1 , can be obtained in the corresponding interval.
[0066] To verify the responsiveness of the compound containing thioacetal bonds (HA-TA-HMF) to ROS, the compound was characterized by NMR. The lyophilized HA-TA-HMF was dissolved in heavy water and incubated with H2O2 solutions of different proportions and concentrations for 6 h, 12 h and 24 h, respectively. The presence of thioacetal responsive characteristic peaks was analyzed by 1H NMR spectroscopy. The specific proportions are shown in Table 1 below.
[0067] Table 1. HA-TA-HMF at different ratios
[0068]
[0069] Weigh 10 mg of HA-TA-HMF lyophilized sample and dissolve it in different proportions of heavy water and H2O2. The solutions are: control group (without H2O2 solution), 0.55 mL of heavy water mixed with 1 mM H2O2, and 0.55 mL of heavy water mixed with 10 mM H2O2. These are named HA-TA-HMF0, HA-TA-HMF1, and HA-TA-HMF2, respectively.
[0070] according to Figure 3As can be seen from the chemical formula, 5-HMF has an aldehyde group, i.e., at position a. When it is attached to a polymer, the aldehyde group will react and disappear. This corresponds to the absence of the characteristic peak of the aldehyde group on the NMR spectrum, i.e., the NMR spectrum of -H2O2. To prove that the attached chemical bond has ROS responsiveness (i.e., H2O2), a certain concentration of H2O2 solution is added. If it is responsive, the chemical bond will break, i.e., 5-HMF will return to its original state, i.e., the aldehyde group will be restored. This will be observed on the NMR spectrum as the aldehyde group peak, i.e., position a in +H2O2 in the figure, at 9-11 ppm. At the same time, the peak shape at the thioacetal bond (position b) will be correspondingly weakened. These two points can simultaneously prove that the ROS response was successfully carried out.
[0071] Example 3
[0072] This embodiment provides a method for preparing conductive hydrogels, specifically including:
[0073] A conductive hydrogel was obtained by crosslinking a compound containing a thioacetal bond (HA-TA-HMF), acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, and PEDOT:PSS.
[0074] Take 50 mg of lyophilized sample and dissolve it in acrylamide solutions with different solid contents. Add a certain proportion of crosslinking agent and conductive medium, and observe the crosslinking of the sample with different proportions of acrylamide solution. These are named groups A, B, C, and D, respectively. After uniform stirring, pour the solution into a mold and perform thermal crosslinking at 80℃ for about 2 hours. After gelation, seal and store at low temperature or room temperature. Specific proportions are shown in Table 2.
[0075] Table 2 shows the different conductive hydrogels prepared.
[0076]
[0077] To verify the responsiveness of the conductive hydrogel to ROS, the conductive hydrogel was characterized accordingly, and the test results are as follows: Figure 4 As shown.
[0078] according to Figure 4The in vitro release within 72 hours confirmed the responsive release of the prepared conductive hydrogel to 5-hydroxymethylfurfural (HMF) under ROS conditions. Twelve identical hydrogels were divided into four groups: PBS, 0.1 mM H2O2, 1 mM H2O2, and 10 mM H2O2. Each group had three parallel samples, for a total of twelve groups. In vitro release experiments were conducted in 45 mL of the medium, with samples taken at 1 min, 30 min, 2 h, 6 h, 12 h, 24 h, 48 h, and 72 h, and their OD values were measured. Based on the standard curve and known absorption peak positions, a maximum absorption peak was observed at 384 nm. The cumulative release was calculated using the formula, showing that the release of 5-HMF from the hydrogel significantly increased with increasing H2O2 concentration, and the release rate accelerated. The PBS control group showed no significant release, demonstrating the responsiveness of the conductive hydrogel under ROS conditions. Furthermore, as the H2O2 concentration increases, the responsiveness of the chemical bonds is enhanced, and more drugs are released, which is in line with the expected trend.
[0079] To verify the mechanical properties of the fabricated conductive hydrogel, stress-strain characterization was performed on the hydrogel, and the test results are as follows: Figure 5 As shown, conductive hydrogels were fabricated into different shapes and subjected to tensile and compression tests to evaluate their mechanical properties. Rod-shaped hydrogel samples (diameter: 15.6 mm, height: 12 mm) were used for static compression tests at a compression rate of 1 mm / min, with the test stopping at 90% compression. Rectangular samples (length: 16 mm, width: 10 mm, height: 1 mm) were used for tensile measurements at a tensile rate of 100 mm / min, with the tensile test ending when fracture occurred.
[0080] according to Figure 5 As can be seen, a) is the tensile stress-strain curve, and b) is the compressive stress-strain curve. According to the tensile stress-strain curve, the first inflection point in the tensile strain is the point of fracture, corresponding to the force on the ordinate. The purpose is to investigate the tensile force that different groups of hydrogels can withstand. According to the figure, when the percentage of PEDOT:PSS added is 0.5%, the hydrogel can withstand the greatest tensile force. According to the compressive stress-strain curve, the first inflection point in the compressive strain is the point of fracture, corresponding to the force on the ordinate. The purpose is to investigate the compressive pressure that different groups of hydrogels can withstand. According to the figure, when the percentage of PEDOT:PSS added is 0.5%, the hydrogel can withstand the greatest compressive pressure. Therefore, group B prepared in this application has the best mechanical properties.
[0081] To verify the electrochemical activity of the fabricated conductive hydrogel, the hydrogel was characterized by electrical signals. The test results are as follows: Figure 6As shown. The prepared conductive hydrogel exhibits sensitive electrochemical activity in the presence of H2O2. Changes in the electrical signal were monitored. All electrochemical measurements were performed at room temperature using an electrochemical workstation (CHI 760E, CH Instruments, USA). A conventional three-electrode system was used, with a gold (Au) electrode as the working electrode, a platinum (Pt) electrode as the counting electrode, and Ag / AgCl saturated KCl as the reference electrode. To determine the H2O2 responsiveness, the equilibrium-expanded conductive hydrogel was immersed in H2O2 solutions of different concentrations (0, 60, 80, 100, 120, 160, 200), and DPV measurements were performed from -0.5V to 0V.
[0082] according to Figure 6 As can be seen, the simulated DPV curve is adjusted for noise and smoothing the tail. DPV measures the sudden changes in current of the sample within a certain potential range. Therefore, when the concentration of H2O2 increases, the intensity of its redox reaction also increases, leading to an increase in the amplitude of the current response. From Figure 6 It is evident that the peak current of the DPV signal increases with increasing H2O2 concentration. Therefore, different concentrations of H2O2 solution will result in different peak currents, thus forming different response gradients.
[0083] To verify the biocompatibility of the prepared conductive hydrogel, cytotoxicity characterization was performed on the hydrogel, and the test results are as follows: Figure 7 As shown. The synthesized hydrogels were grouped into four groups based on their different stages: Control group, HA Hydrogel group, HA-TA-HMF Hydrogel group, and HTH-PEDOT:PSS Hydrogel group. The biocompatibility and toxicity of the hydrogels were investigated using a CCK-8 cytotoxicity assay, with the specific steps as follows:
[0084] Cells were counted (approximately 10,000-25,000 cells per well), and seeded into 24-well plates at 500 μL per well after re-rotation using complete culture medium. Each group was replicated (to minimize error), and the plates were incubated at 37°C for 24 h. The culture medium was then aspirated, and an equal volume of fresh culture medium was added. Pre-prepared, UV-sterilized hydrogels were then placed into the plates and co-incubated for 24 h. Finally, the old culture medium was aspirated from the plates, the material was removed, and diluted Cell Counting Kit-8 solution was added to each well at 400 μL. The plates were incubated for 4 h (this process was conducted in the dark), and the liquid was aspirated into 96-well plates at 100 μL per well, according to the group assignments. The OD value was measured at 450 nm.
[0085] according to Figure 7As can be seen, the control group was the blank group without hydrogel, while the latter three groups synthesized hydrogels at different stages. The final conductive hydrogel was the rightmost group (HTH-PEDOT: PSS, HA-TA-HMF is abbreviated as HTH). According to the test results, a decrease in cell viability greater than 30% was considered cytotoxic. Figure 7 As can be seen, even the second group, with the lowest cell survival rate, still had a survival rate of over 90%, while the survival rates of the remaining groups were all around 98%. Therefore, the conductive hydrogel prepared in this application is considered to have no cytotoxicity and meets biocompatibility safety standards. Furthermore, statistical analysis shows that there was no significant difference overall, but there was a significant difference between the two groups above the 95% level, which meets statistical requirements.
[0086] Therefore, the preparation method provided in this application involves cross-linking a compound containing thioacetal bonds, which forms a monolayer hydrogel network of thiomethyl hyaluronic acid and 5-hydroxymethylfurfural, with acrylamide, N,N'-methylenebisacrylamide, ammonium persulfate, and a conductive medium. The conductive hydrogel prepared in this application exhibits good ROS responsiveness, and its drug release rate is positively correlated with ROS concentration. This enables real-time monitoring of wounds, achieving integrated diagnosis and treatment of chronic wounds, alleviating inflammatory responses, and promoting wound healing. Furthermore, it possesses excellent mechanical properties and biocompatibility, showing broad application prospects in the preparation of biomedical materials.
[0087] The various embodiments in this specification are described in a progressive manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0088] The above embodiments are only used to illustrate the technical solutions of this application, and are not intended to limit this application. Although this application has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein. Such modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of this application.
Claims
1. A method for preparing a ROS-responsive conductive hydrogel, characterized in that, The preparation method includes: Thiolized hyaluronic acid, 5-hydroxymethylfurfural, and trifluoroacetic acid were dissolved in water and reacted. After the reaction was completed, the mixture was purified by dialysis to obtain a compound containing a thioacetal bond. The compound containing thioacetal bonds, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate were crosslinked with a conductive medium to obtain a conductive hydrogel with ROS response. The method for preparing the thiolized hyaluronic acid includes: Hyaluronic acid, cystamine dihydrochloride and 1-hydroxybenzotriazole hydrate were dissolved in polybutylene succinate, the pH was adjusted, and 1-ethyl-(3-dimethylaminopropyl)carbodiimide hydrochloride and dithiothreitol were added to react and purified by dialysis to obtain thiolized hyaluronic acid. The pH value is adjusted within the range of 7.5-8.5; The reaction is carried out under light-protected conditions at room temperature after dissolving mercapto-modified hyaluronic acid, 5-hydroxymethylfurfural and trifluoroacetic acid in water. The percentage of acrylamide added is 16-26%; The amount of N,N'-methylenebisacrylamide added is 10% of the acrylamide monomer; The conductive medium is poly(3,4-ethylenedioxythiophene):polystyrene sulfonate; the amount added is 0.2-1%; When the compound containing thioacetal bonds, acrylamide, N,N'-methylenebisacrylamide, and ammonium persulfate are crosslinked with a conductive medium, the reaction temperature is 60-80℃ and the reaction time is 1.5-4h.
2. A conductive hydrogel prepared by the preparation method of claim 1.
3. The application of a conductive hydrogel prepared by the preparation method of claim 1 or the conductive hydrogel of claim 2 in the preparation of biomedical materials.
Citation Information
Patent Citations
Antibacterial antioxidant conductive adhesive hydrogel as well as preparation method and application thereof
CN115010998A
Conductive eutectic gel, preparation method thereof and application of conductive eutectic gel in preparation of preparation for treating burn
CN118063698A